Preliminary Study of Sars-Cov-2 Occurrence in Wastewater in the Czech Republic - Mlejnkova, Hana; Sovova, Katerina; Vasickova, Petra; Ocenaskova, Vera; Jasikova, Lucie; Juranova, Eva (International journal of environmental research and public health, 2020)
The virus SARS-CoV-2, which has caused the recent COVID-19 pandemic, may be present in the stools of COVID-19 patients. Therefore, we aimed to detect SARS-CoV-2 in wastewater for surveillance of SARS-CoV-2 in the population. Samples of untreated wastewater were collected from 33 wastewater treatment plants (WWTPs) of different sizes within the Czech Republic. SARS-CoV-2 RNA was concentrated from wastewater and viral RNA was determined using real-time reverse transcription polymerase chain reaction (RT-qPCR). SARS-CoV-2 RNA was detected in 11.6% of samples and more than 27.3% of WWTPs; in some of them, SARS-CoV-2 was detected repeatedly. Our preliminary results indicate that an epidemiology approach that focuses on the determination of SARS-CoV-2 in wastewater could be suitable for SARS-CoV-2 surveillance in the population.
Keywords: Coronavirus Infections; coronavirus; feces; SARS-CoV-2; Feces; wastewater; Wastewater; RNA, Viral; RT-qPCR; wastewater-based epidemiology; lidé; koronavirové infekce; COVID-19; virus; Pneumonia, Viral; odpadní voda; Betacoronavirus; epidemic; virová pneumonie; pandemie; RNA virová; Czech Republic; Waste Water; Česká republika; early warning system; Pandemics; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; Humans